Optimizing total RNA extraction method for human and mice samples - Zeng, Yumei; Tang, Xiaoxue; Chen, Jinwen; Kang, Xi; Bai, Dazhang (PeerJ, 2024)
Background Extracting high-quality total RNA is pivotal for advanced RNA molecular studies, such as Next-generation sequencing and expression microarrays where RNA is hybridized. Despite the development of numerous extraction methods in recent decades, like the cetyl-trimethyl ammonium bromide (CTAB) and the traditional TRIzol reagent methods, their complexity and high costs often impede their application in small-scale laboratories. Therefore, a practical and economical method for RNA extraction that maintains high standards of efficiency and quality needs to be provided to optimize RNA extraction from human and mice tissues. Method This study proposes enhancements to the TRIzol method by incorporating guanidine isothiocyanate (GITC-T method) and sodium dodecyl sulfate (SDS-T method). We evaluated the effectiveness of these modified methods compared to the TRIzol method using a micro-volume UV-visible spectrophotometer, electrophoresis, q-PCR, RNA-Seq, and whole transcriptome sequencing. Result The micro-volume UV-visible spectrophotometer, electrophoresis, and RNA-Seq demonstrated that the GITC-T method yielded RNA with higher yields, integrity, and purity, while the consistency in RNA quality between the two methods was confirmed. Taking mouse cerebral cortex tissue as a sample, the yield of total RNA extracted by the GITC-T method was 1,959.06 ± 49.68 ng/mg, while the yield of total RNA extracted by the TRIzol method was 1,673.08 ± 86.39 ng/mg. At the same time, the OD260/280 of the total RNA samples extracted by the GITC-T method was 2.03 ± 0.012, and the OD260/230 was 2.17 ± 0.031, while the OD260/280 of the total RNA samples extracted by the TRIzol method was 2.013 ± 0.041 and the OD260/230 was 2.11 ± 0.062. Furthermore, q-PCR indicated that the GITC-T method achieved higher yields, purity, and greater transcript abundance of total RNA from the same types of animal samples than the TRIzol method. Conclusion The GITC-T method not only yields higher purity and quantity of RNA but also reduces reagent consumption and overall costs, thereby presenting a more feasible option for small-scale laboratory settings.
Keywords: Total RNA extraction method; TRIzol reagent; The TRIzol method; GITC-T method; SDS-T method